Modern Family Types - Mavjuda Bekbutayevna Burkhanova (Euro Asian Journal Publishing, 2024)
This article analyzes issues such as types of families, in particular single and large families, characteristics of family environment, influence on intellectual and personal development of children in these families, internal family relations of large families and families with only one child
Keywords: family; family environment; family types; child